(untitled) (Fiep Bulletin - online, 2016)
The objective of this study was to verify and compare the movement time in Physical Education classes, with students of both genders in Middle School in the public school system in the city of Vitória, ES. The study group contained 30 students, 15 males aged 10 on average (±=0.70) aged 9.87 on average (±= 0.67). In the execution of this research, the following instruments were used: chronometers, clipboards and pens. The classes were 50-minute long and upon the start of the teacher’s activities, the timing on the chronometer would also be started and paused when the subjects were still. Whenever the students would start moving again, timing on the chronometer would be resumed, and so on until the end of class. The data was collected by two university students through observation from afar, who had been chosen by means of a draw. The results showed that the movement time was an average of 15.1 (±:7.4) minutes for the boys and 14.09 minutes (±:6.6) for the girls. Based on the data analysis and also on the literature (WEINECK, 2005; WILMORE & COSTILL, 2001) the conclusion is that the groups’ average movement time in Physical Education classes is not enough to provide positive adaptations in the relation between exercise and health.